IGF-2 coated porous collagen microwells for the culture of pancreatic islets. Issue 2 (20th December 2016) - Forget, A.; Waibel, M.; Rojas-Canales, D. M.; Chen, S.; Kawazoe, N.; Harding, F. J.; Loudovaris, T.; Coates, P. T. H.; Blencowe, A.; Chen, G.; Voelcker, N. H.
Abstract : A new platform for the culture of pancreatic islets that improves the cell viability and quality. Paving the way for a highly efficient islet clinical transport. Abstract : Islet transplantation, the only curative therapy for type I diabetes, requires isolation of the graft in highly specialized facilities for its later dispatch to remote transplantation centres. During transport and culture, many valuable cells are lost due to several factors such as mechanical stress, islet aggregation and dissociation. Here, we evaluate a porous microwell array sheet made of natural collagen type I extracellular matrix (ECM) protein as a novel islet culture substrate. This culture platform can be coated with IGF-2, a growth factor favorable for islet survival, and allows segregation of the islets within the porous microwell sheet, preventing aggregation. This design shows promising results for improving human pancreatic islets viability and function during culture and could form a novel paradigm for the transport of islets between isolation and transplantation centres.